2010
DOI: 10.1016/s1607-551x(10)70009-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Esophageal Variceal Hemorrhage

Abstract: Acute esophageal variceal hemorrhage (AEVH) is a devastating complication of portal hypertension. Evaluation of the natural history of AEVH showed that it is associated with a mortality rate of 40%, and a high incidence of early rebleeding of 30-50% among the survivors [1]. The factors responsible for AEVH are not well known. Portal pressure, variceal pressure, and the tension of the esophageal variceal wall have been demonstrated to be associated with AEVH. Hepatic venous pressure gradient (HVPG) > 12 mmHg is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 82 publications
(119 reference statements)
0
13
0
1
Order By: Relevance
“…Subsequently, pantoprazole 40 mg tablet was administered orally for 14 days. Standard therapy, including blood and frozen plasma transfusion, fluid and electrolytes replacement, and prophylactic antibiotics (cefazolin 1 gm q6 h for 5 days) and lactulose were administered to patients in both groups as clinically indicated . All the patients signed an informed consent.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, pantoprazole 40 mg tablet was administered orally for 14 days. Standard therapy, including blood and frozen plasma transfusion, fluid and electrolytes replacement, and prophylactic antibiotics (cefazolin 1 gm q6 h for 5 days) and lactulose were administered to patients in both groups as clinically indicated . All the patients signed an informed consent.…”
Section: Introductionmentioning
confidence: 99%
“…The initial management of AVB includes standard resuscitation measures in addition to the use of intravenous vasoconstrictors, such as Octreotide, followed by endoscopic therapy [20][21][22][23][24] . This will control the bleeding in the majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This will control the bleeding in the majority of patients. However, in cases where the bleeding is not controlled by initial measures, emergency transjugular intrahepatic portosystemic shunt is the best alternative in those who can tolerate the procedure [20,21,23] . Only 3 of our patients had emergency surgery for refractory variceal bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the time interval of band ligation remains an unsettled issue. Although some studies proposed an interval of 1 to 2 weeks [69, 70, 74], others advocated an interval of 1-2 months of band ligation for obliteration of EV [75, 76]. Yoshida et al found a short interval between sessions of EVL might even be detrimental by showing that the overall rates of variceal recurrence and additional treatment were both higher in patients with EVL at a biweekly interval than those with a bimonthly protocol [76].…”
Section: Endoscopic Therapy For Secondary Prophylaxismentioning
confidence: 99%